Novel variant alters splicing of TGFB2 in family with features of Loeys-Dietz syndrome - Gordon, Emily R.; Felker, Stephanie A.; Coleman, Tanner F.; Sosonkina, Nadiya; Pugh, Jada; Cochran, Meagan E.; Hurst, Anna C. E.; Cooper, Sara J. (Frontiers in Genetics, 2024)
Loeys-Dietz syndrome (LDS) is a connective tissue disorder representing a wide spectrum of phenotypes, ranging from isolated thoracic aortic aneurysm or dissection to a more severe syndromic presentation with multisystemic involvement. Significant clinical variability has been noted for both related and unrelated individuals with the same pathogenic variant. We report a family of five affected individuals with notable phenotypic variability who appear to have two distinct molecular causes of LDS, one attributable to a missense variant in TGFBR2 and the other an intronic variant 6 bp upstream from a splice junction in TGFB2. We tested the functional impacts of the variant identified in the proband alongside other variants in the region reported in ClinVar using a splice reporter system, which resulted in non-canonical splicing products for several variants including the proband. Molecular validation of the splicing products suggests that the TGFB2 variants tested impact splicing by reducing efficiency of the canonical acceptor in favor of an alternate acceptor within the exon. These data combined with clinical phenotypes and segregation of the variant with disease support the conclusion that this intronic TGFB2 variant may cause LDS in this patient and her mother. These analyses demonstrate that underappreciated intronic variants that alter splicing can be relevant for clinical phenotypes of connective tissue disease. This case highlights the importance of prompt familial cascade testing, clinical evaluation with detailed dysmorphology exam, comprehensive genetic testing, and collaboration between clinicians and scientists to characterize variants of uncertain significance to properly assess risk in LDS patients.